A study of water depth on the growth and productivity of seaweed Kappaphycus alvarezii - Kasnir, Muhammad; Syarifuddin, Syarifuddin; Nisaa, Khairun (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2023)
This study aims to investigate the impact of varying the depth of water on the growth and productivity of seaweed Kappaphycus alvarezii. The study was carried out in the seas of Pallette. The research methodology used in this study incorporates three different planting depth treatments, specifically 1.5 meters, 3 meters, and 4 meters. In each treatment, 50 grams of Kappaphycus alvarezii seeds per bunch were used. The findings of this study indicate that seaweed cultivation at a depth of 1.5 m yields significantly favourable outcomes compared to the treatments conducted at depths of 3 m and 4 m, where growth is comparatively less optimal. This occurrence can be attributed to the diminished level of light penetration at such a depth. There is an inverse relationship between the depth of seaweed planting and the rate of weight gain. The optimal depth for seaweed cultivation for 42 days is 1.5 meters, with an average specific growth rate of 3% daily. On the contrary, the treatment carried out at a depth of 1.5 m showed the most substantial increase in biomass, averaging 122 g. Additionally, the maximum yield of seaweed was observed in the same treatment, precisely measuring 1,208 g/m2.